Analysis of the psychometric properties of the Buss-Perry Aggression Questionnaire (AQ) in Colombian adolescents (2023)
The psychometric properties of the Buss and Perry AQ questionnaire of aggression, one of the most used questionnaires worldwide to measure aggressive behavior, were examined in a sample of adolescents (n=779 participants) from the cities of Barranquilla (n= 410) and Pereira (n= 369), in Colombia. In total, 752 participants (Mean age of 15.3 years, SD = 1.9; 57,4%. women and 42,6 men) completed the Buss and Perry AQ questionnaire. Subsequently, the univariate and multivariate normality of the items was evaluated, and a confirmatory factor analysis (CFA) was performed on the data set. Likewise, the fit of two models was evaluated, a multidimensional a priori model, and a model with a second-order factor (aggressive behavior), which could explain the variance of the items. Finally, the reliability indices of the questionnaire were identified. The results showed acceptable goodness-of-fit indices (X2/df = 2.29, CFI = .977, IFI = .977, GFI = .984, AGFI = .979, RNI = .984, NFI = .972, RMSEA of .047 [90% CI = .016 - .036] and SRMR = .059) for the second-order one-factor model, as well as acceptable reliability indices (?= .55 - .88). In conclusion, these results show that the scale can be applicable to Colombian preadolescents and adolescents, but warn of the limitations of its use for the non-aggression subscale. Nevertheless, the application of the scale in its original version is suggested to determine its psychometric behavior.